FIRST AID IN HYPERTHERMIC SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the basic principles of first aid in hyperthermic syndrome, the importance of prompt action, and practical steps. Hyperthermia occurs when the body temperature rises dangerously, seriously affecting the central nervous system, cardiovascular function, and respiratory processes. In this case, early detection and proper first aid are important factors in saving the patient's life. The article discusses the rules for removing the patient from the risk factor, gradually lowering body temperature, administering fluids, as well as actions to be taken in the event of complications such as fainting, convulsions, or respiratory failure. The need to call for emergency medical help is also emphasized.